If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(6 + 3x) = 84 (6 * 7 + 3x * 7) = 84 (42 + 21x) = 84 Solving 42 + 21x = 84 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 21x = 84 + -42 Combine like terms: 42 + -42 = 0 0 + 21x = 84 + -42 21x = 84 + -42 Combine like terms: 84 + -42 = 42 21x = 42 Divide each side by '21'. x = 2 Simplifying x = 2
| 2(-11-18q)= | | 6(5-8v)+12=-15 | | (2w-3)+w=78 | | 4(7v-4)-8=144 | | -2=5+3x | | y+2y+3y=150+(-12) | | y-9x=10 | | 4x+2x+x=42 | | 7-7n-2n=-8n+2 | | 7y*y= | | 2(5s+6)-4s=3(2s+3)-10 | | (a-b)(2a+ab)= | | 10(4h-16)= | | 8x+y=2x | | 6x^2-24x^2=0 | | 8t+2=t+5+t-3 | | 4n-2.8=8.8 | | 72=.75m | | 24/6*4= | | 11x-3=4x-52 | | 0.13y+0.08(y+5000)=2080 | | x^2-3ix-2=2 | | x^2-300x+3500=0 | | 5x+5+7x+19=36 | | 20=-5(5+4x)-5(1+6x) | | 6(-13+-17c)= | | 8(x+2)=4(2x+2)+8 | | xy=4y | | x^2+-x^2=0 | | w-3w=w-2 | | q=G-Gsz | | 3p-7+5p=9 |